Expression Pattern Analysis of Antiviral Genes and Inflammatory Cytokines in PEDV-Infected Porcine Intestinal Epithelial Cells - Wang, Shiqin; Wu, Jiayun; Wang, Fang; Wang, Haifei; Wu, Zhengchang; Wu, Shenglong; Bao, Wenbin (Frontiers in Veterinary Science, 2020)
Porcine diarrhea disease in newborn and suckling piglets due to infection with porcine epidemic diarrhea virus (PEDV) is a leading cause of economic loss in the pig industry globally. In this study, we investigated the molecular mechanism of the host innate immune response to PEDV infection. The expression dynamics of antiviral genes (e.g., RIG-1, PKR, OAS1, Mx1, and Mx2) and inflammatory cytokines (e.g., IFN-α, IFN-β, TNF-α, IL-6, IL-8, and IL-12) in porcine small intestinal epithelial (IPEC-J2) cells were analyzed following PEDV stimulation. The results showed that the expression of antiviral genes (e.g., PKR, OAS1, and Mx2) and inflammatory cytokines (e.g., IFN-α and TNF-α) were significantly reduced within 0 to 4 h post-infection (P < 0.05). However, all antiviral genes and inflammatory cytokines were up-regulated from 12 - 24 h (P < 0.05), and cytopathic changes were observed during this time. The expression of RIG-1, PKR, OAS1, Mx1, and Mx2 were significantly and positively correlated to each other during the entire infection (P < 0.01). The results suggest that the RIG-1, PKR, OAS1, Mx1, and Mx2 genes play an important role in PEDV infection in piglets. Initially, PEDV displayed cellular invasion by inhibiting IFN-α transcription and interfering with the antiviral function of PKR, OAS1, and Mx2, ultimately inducing an intense inflammatory response. The relationship between antiviral genes and inflammatory cytokines with PEDV infection at the cellular level provides a reference for studying the mechanism of resistance to PEDV infection in piglets.